2007
DOI: 10.1590/s0103-97332007000800004
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent photoluminescence spectra of GaAsSb/AlGaAs and GaAsSbN/GaAs single quantum wells under different excitation intensities

Abstract: The mechanism for low-temperature photoluminescence (PL) emissions in GaAsSb/AlGaAs and GaAsSbN/GaAs strained-layer single quantum wells (SQWs), grown by molecular-beam epitaxy, is studied in detail, using PL spectroscopy as a function of temperature and excitation intensity. In all samples, the PL peak energy as well as the full width at half maximum (FWHM), as a function of temperature, present anomalous behaviors, i.e., the PL peak energy shows a successive red/blue/redshift (S-shaped behavior) and the FWHM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 49 publications
6
23
0
Order By: Relevance
“…This S-shape behavior has already been observed by several authors [30][31][32][33] and has been attributed to localized exciton (LE) by potential fluctuations induced by random distribution of impurities, defects and alloy disorder in samples [34]. The S-shape disappears in the case of PSF22 sample where E PL (T) presents a temperature variation according to BoseEinstein model [35] (See Fig.…”
Section: Pl Temperature Dependencesupporting
confidence: 66%
“…This S-shape behavior has already been observed by several authors [30][31][32][33] and has been attributed to localized exciton (LE) by potential fluctuations induced by random distribution of impurities, defects and alloy disorder in samples [34]. The S-shape disappears in the case of PSF22 sample where E PL (T) presents a temperature variation according to BoseEinstein model [35] (See Fig.…”
Section: Pl Temperature Dependencesupporting
confidence: 66%
“…This phenomenon was also observed in GaAs/ AlGaAs and GaAsSb/ AlGaAs simple QWs, 17,18 and it was interpreted as competition between the blueshift ͑due to potential fluctuations͒ and the redshift ͑due to band-gap renormalization͒. The temperature T X at which the crossing takes place was interpreted as a point where the competition between the mechanism of band-gap renormalization and potential fluctuation is at its maximum.…”
Section: Discussionmentioning
confidence: 72%
“…Below T X , the potential fluctuations dominate the excitonic transitions, and for temperature values superior than T X , the effect of band-gap energy renormalization starts to predominate. 18,19 Taking this into account, it can be observed that on ͑311͒ surfaces, the values of T X are higher than those on ͑100͒, showing that the potential fluctuations are higher in those surfaces.…”
Section: ͑4͒mentioning
confidence: 95%
See 2 more Smart Citations